BANK CREDIT AND IT’S ROLE IN THE IMPLEMENTATION OF NATIONAL PROJECTS - Kozhomkulova A. K.; Torokulova N. D. (Vestnik Issyk-Kulʹskogo universiteta)
This article discusses the importance of the banking system and the financial sector as a whole in the implementation of national projects, and analyzes the current activities of banks to develop human capital, accelerate economic growth and digitalize their activities. At the current stage of development of the Kyrgyz economic system, more and more attention is paid to the problems of transition to the path of stable development. Therefore, in the general ideology of the sustainability of the development of bank lending in the Kyrgyzstan several main goals can be identified, which are largely related to priority national projects. Ensuring accessibility of financial services for all members of society is an important socio-economic task. Increasing the penetration of financial services contributes to the growth of the financial market and the development of competition, stimulates economic growth. Particular attention needs to be paid to improving the speed and quality of access to financial services for consumers in remote areas and rural areas, SMEs and groups with limited access to financial services.